Effect of the fungus Aspergillius spp. and magnetized water on NPK percentage content and yield in wheat (Triticum aestivum L.) - AL-Shebly, Hayder Azeez Ali; AL-mehana, Wisam Naji Atiyah; Ali, Amel Ajel (Journal of Kerbala for Agricultural Sciences, 2018)
An experiment was conducted in the collage of Agriculture ,University of kufa , during the growing season of 20016-2017 to study the effects of irrigation with magnetized water(MW) at density level of 1600 gauss, the fungus Aspergillus and the herbicide Granstar (at 50% and 100% of the recommended dose) on wheat growth parameters and yield. Results showed that Aspergillus spp interacted with MW significantly resulted in the highest values of NPK content and yield compared to the lowest values from the Granstar and weedy control treatments with and without MW, respectively. On the other hand, irrigation with MW always resulted in higher values of tested parameters than that those irrigated with regular water, all treatments interacted with MW had better and higher effects compared to of those interacted with regular water. The study showed that using the bio-controlling agent Aspergillius spp decreased weed and increased wheat growth. and using magnetized water is useful for better growth parameters and yield in wheat fields.